Perceived value of bargain shopping among youth / Nadia Hanim Mohd Wasilan - Mohd Wasilan, Nadia Hanim (2013)
Shopping is acknowledged as an enjoyable activity where most of the countries applying the concept of shopping “festivals”, “carnivals” and “seasons”. This shopping seasons is eagerly awaited by locals and visitors as to grab the great discount and promotions, bargains and unbelievable discounts. Youth are one of the potential segment that should not be overlooked. Youth are those who aged 18 to 30 years old which formerly known as youth shopper. They are an emerging group that is recognized as a meaningful market segment as they have high spending power. Due to the recession, consumer had changed their mindset about discounted goods as nowadays, they are looking for good deals. The concept of customer perceived value used for more sophisticated measures of the construct. This study endeavours to investigate the relationship between youth perceived value attributes of bargain shopping towards future intention. Yet, there is a lack of studies pertaining to their perceived value of bargain to youth especially the youth excursionist. The findings may help the retailers to understand the youth shopping behaviour and refurbish their strategies as to attract youth spend in Malaysia. The results offer significant implications for retailers and future research in this strategically important area.